Dental Prosthetic Treatments in Cleidocranial Dysplasia: Case Report and Literature Review - Yosra Mabrouk; Sinda Ammar; Amel Labidi; Lamia Mansour; Sonia Ghoul (Hindawi Limited, 2020)
Cleidocranial dysplasia (CCD) is a rare inherited skeletal syndrome. There is no consensus regarding the dental treatment strategy. Objectives. To report a rare case of cleidocranial dysplasia and to summarize the current clinical and dental features and prosthetic treatment of similar CCD patients reported in the literature. Results. A 17-year-old girl was diagnosed with CCD. She had a short stature with the ability to bring the shoulders under the chest. All remaining teeth were deciduous except the four first molars were permanent. The maxilla was hypoplastic with a relative prognathism of the mandible. The cone-beam computed tomography examination showed a distorted and incomplete root formation of the permanent teeth. She was treated with both, complete and partial, removable overdentures. PubMed was used for the literature research using the following keys words "Cleidocranial Dysplasia"[Mesh], "Prosthodontics"[Mesh], "Dental Care"[Mesh], "cleidocranial dysostosis," and "dental treatment." The retention of deciduous teeth was described in the majority of cases. All the patients had supernumerary teeth. The most used treatments were dental prosthetics and orthodontics. The fixed prosthetic implant was the most used type of prosthetic treatment. Among the 15 cases who specified the type of prosthetic treatment, seven patients received removable dentures. Prosthetics was indicated especially for aged patients. Conclusion. Removable prostheses are a good solution that rapidly restores esthetics and functions. The use of implants for these patients needs to be validated by a long-term follow-up.